Sosialisasi Strategi Pemasaran Kerajinan Souvenir Menggunakan Media Online di Era Pandemi Virus Covid-19 - Anindita Trinura Novitasari; Rica Wijayanti; Yusrianto Sholeh (STKIP Andi Matappa, 2021)
This community service program is motivated by the decreased number of souvenir sales by the micro, small and medium enterprises (UMKMs) in Martajasah Village where the program takes place. This condition is mainly caused by the rise of global Covid-19 pandemic. Solution provided by this community service is to offer the UMKMs to switch from conventional direct sale to online sale. The method of this program is direct dissemination reaching out to the craftsmen to introduce online marketing. The outcome of this community service program is to enable the souvenir UMKMs practice any online marketing method using WhatsApp, Facebook, Instagram, and other social media platforms by disseminating the introduction of virtual marketing media